Pengaruh Jenis Bakteri Pelarut terhadap Pertumbuhan dan Hasil Benih G3 Kentang (Solanum tuberosum L.) Varietas Medians. - Indriana Ulfah; Linlin Parlinah; Noertjahyani Noertjahyani; Rohana Abdullah (Paspalum: Jurnal Ilmiah Pertanian, 2020)
This article aims to examine the effect of phosphate solubilizing bacteria (PSB) on the growth and yield of G3 seeds of potato (solanum tuberosum L.) varieties of medians. The experiment was conducted in the experimental garden of The Faculty of Agriculture of Winaya Mukti University Tanjungsari, Sumedang with a height of 850 meters above sea level with the order of land Andisol. Time trials are conducted from May to August 2019. The design used is a simple RandomIzed Group Design consisting of five types of phosphate Solubilizing bacteria, namely without PSB, Pseudacidovorax intermedius, Agrobacterium fabrum, Agrobacterium tumefaciens, Serratia nematodiphila and repeated five times each. The results of the experiment showed that the administration of this type of PSB was able to increase the height of the plant and the number of leaves at the age of 28 DAP and 42 DAP and give the result of the number of potatoes and the weight of the perpetak tubers on the potato crop of the medians varieties better.